Українська емігрантська історіографія ХХ ст. про В. Д. Отамановського - Робак, І.Ю.; Демочко, Г.Л. (Історичний архів. Наукові студії, 2013)
Розглянуто історичні розвідки представників української діаспори у Канаді та США,
зокрема, праці Р. Млиновецького та П. Мірчука. Проаналізовані ті роботи, які
стосуються діяльності В. Д. Отамановського – видатного учасника українських
визвольних змагань 1917-1918 рр. Відтворені цікаві факти діяльності майбутнього
вченого і організатора науки, зокрема визначена його роль у створенні Української
Центральної Ради. Рассмотрены исторические работы представителей украинской диаспоры в Канаде
и США, а именно, работы Р. Млиновецкого и П. Мирчука. Проанализированы те работы,
в которых рассматривается деятельность В. Д. Отамановского – выдающегося участника
украинского освободительного движения 1917-1918 гг. Отображены интересные
факты деятельности будущего ученого и организатора науки, определена его роль в
создании Украинской Центральной Рады. Valentin Otamanovsky name has been undeservedly forgotten for many years. He was
known in Ukraine above all as a public figure. Foreigner historiographers started to investigate
his public activity and scientific heritage early then Soviet scientists.
Peter Mirchuk and Roman Mlinovetsky were the first Ukrainian historiographers in the USA
who analyzed Otamanovsky’s biography, beliefs and aspirations, his scientific papers. Thanks to
their research, the name of Valentine Otamanovsky entered the most famous emigrant
encyclopaedia.
The purpose of this study – a historical overview of P. Mirchuk and R. Mlinovetsky
researches, which showed Valentin D. Otamanovsky political activity. We also studied the other
Diaspora historians works, which were dialled with Otamanovsky investigation.